DEVELOPMENT OF INDONESIAN WORK READINESS SCALE ON FRESH GRADUATE IN INDONESIA - Sagita, Marisa Putri; Hami, Azhar El; Hinduan, Zahrotur Rusyda (Faculty of Psychology, Diponegoro University, 2020)
Fresh graduates need to have work readiness as one of the essential attributes. Work readiness is a condition when fresh graduates ready to succeed in the working world. In Indonesia, studies explaining the measurement scale of work readiness are still limited. This study aims to develop a work readiness scale for undergraduates, which is beneficial for companies, universities, and fresh graduates. The research sample consists of 118 fresh graduates, with no prior work experiences. After several examinations, the scale contains 49 items. As a result, the construct validity test using confirmatory factor analysis (CFA) shows that the developed instrument can measure the work readiness construct. The results of the reliability test using Cronbach's alpha coefficient is .961. This number means that the developed instrument is reliable. The analysis results show that the developed work readiness scale has good validity and reliability.